Epigenetic and Genetic Factors Associated With Opioid Use Disorder: Are These Relevant to African American Populations - Blackwood, Christopher A.; Cadet, Jean Lud (Frontiers in Pharmacology, 2021)
In the United States, the number of people suffering from opioid use disorder has skyrocketed in all populations. Nevertheless, observations of racial disparities amongst opioid overdose deaths have recently been described. Opioid use disorder is characterized by compulsive drug consumption followed by periods of withdrawal and recurrent relapses while patients are participating in treatment programs. Similar to other rewarding substances, exposure to opioid drugs is accompanied by epigenetic changes in the brain. In addition, genetic factors that are understudied in some racial groups may also impact the clinical manifestations of opioid use disorder. These studies are important because genetic factors and epigenetic alterations may also influence responses to pharmacological therapeutic approaches. Thus, this mini-review seeks to briefly summarize what is known about the genetic bases of opioid use disorder in African Americans.